Spindle associated membrane protein 1 (Samp1) is required for the differentiation of muscle cells. Issue 1 (December 2017) - Jafferali, Mohammed; Figueroa, Ricardo; Hasan, Mehedi; Hallberg, Einar
Abstract Muscles are developed and regenerated in a differentiation process called myogenesis, which involves components of the nuclear envelope. We have investigated Samp1 (Spindle Associated Membrane Protein 1), a transmembrane nuclear envelope protein, which interacts with emerin and lamin A, both of which are linked to Emery-Dreifuss muscular dystrophy (EDMD). We found that the levels of Samp1 increased seven-fold during differentiation of mouse C2C12 muscle progenitor cells. To test if Samp1 could have a role in myogenesis we developed stable C2C12 knockdown cell lines expressing short hairpin RNA targeting Samp1 expression. The Samp1 depleted C2C12 cells displayed normal mobility and normal distribution of emerin and lamin A. However, Samp1 depletion increased ERK signaling and completely blocked differentiation of C2C12 cells, which failed to express myogenic marker proteins and failed to form myotubes. The block in myogenesis in Samp1 depleted cells was completely rescued by ectopic expression of RNAi resistant human Samp1, showing that Samp1 is required for muscle differentiation.